Healthcare Access vs. Quality Healthcare: Rethinking Healthcare Risks - Augustine Kumah (Public Health Reviews)
ObjectivesThis narrative literature review examines the global burden of mortalities due to poor quality care compared to mortalities resulting from lack of access to healthcare, focusing on the period from 2015 to 2024.MethodsData was extracted from electronic databases such as PubMed, Google Scholar, Scopus, Ebscohost, and WHO. Relevant statistics on mortality rates due to poor quality care and lack of access to healthcare from the identified data sources were extracted. Descriptive statistics were used to summarize the mortality rates, with trends analyzed over the 10 years.ResultsThe results indicate that while progress in healthcare access has reduced mortality, the lack of corresponding improvements in care quality has led to a rising number of preventable deaths. The findings reveal a consistent decline in mortality due to lack of access. In contrast, mortality due to poor quality care has increased from 5 million in 2015 to an estimated 6 million by 2024, underscoring the persistent challenges in healthcare delivery, including medical errors, misdiagnoses, and inadequate treatment.ConclusionAddressing the dual challenges of access and quality is essential for reducing global mortality rates and achieving better health outcomes.